2009
DOI: 10.1016/j.gca.2008.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Newly recognized hosts for uranium in the Hanford Site vadose zone

Abstract: Uranium contaminated sediments from the U.S. Department of Energy's Hanford Site have been investigated using electron microscopy. Six classes of solid hosts for uranium were identified. Preliminary sediment characterization was carried out using optical petrography, and electron microprobe analysis (EMPA) was used to locate materials that host uranium. All of the hosts are fine-grained and intergrown with other materials at spatial scales smaller than the analytical volume of the electron microprobe. A focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 42 publications
0
75
0
Order By: Relevance
“…[14][15][16][17] Owing to the higher solubility of uranyl-phosphate minerals compared with uranyl-arsenates (with solubility products of 10 −12.8 and 10 −49.2 for metatorbernite and metazeunerite, respectively), 24 it might be expected that arsenate end-members of this mineral family would dominate over the phosphate end-members, which is indeed observed in the Rietveld analysis of data shown in Fig. 3b, and composition inferred from interpolation of the unit cell volume of the end members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16][17] Owing to the higher solubility of uranyl-phosphate minerals compared with uranyl-arsenates (with solubility products of 10 −12.8 and 10 −49.2 for metatorbernite and metazeunerite, respectively), 24 it might be expected that arsenate end-members of this mineral family would dominate over the phosphate end-members, which is indeed observed in the Rietveld analysis of data shown in Fig. 3b, and composition inferred from interpolation of the unit cell volume of the end members.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming the solid solution to follow Vegards Law, our unit cell volume suggests 18% solid solution of metatorbenite in metazeunerite. Metatorbernite has previously been reported to sequester uranium at other uranium-contaminated sites such as Hanford (USA) [14][15][16][17] and has also been reported to occur at South Terras 3 . Although the occurrence of metazeunerite at South Terras has been previously inferred, 18 to our knowledge, this study provides conclusive and verifiable evidence for this phase at the site, and indeed for any studied uranium-contaminated vadose sediments.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Stubbs et al [2] identified metatorbernite, Cu(H 2 O)[(UO 2 ) 2 (PO 4 ) 2 ], and five other hosts for U 6+ in contaminated sediments at the Hanford site. The above results suggest that interactions of these hosts with the local pore water (pH 7.2, Um et al [60]) result in the formation of nanometer-thick coatings of uranyl minerals on the surface of each host.…”
Section: Neutral and Basic Conditionsmentioning
confidence: 99%
“…These minerals are important in controlling the mobility of uranium in the contaminated subsurface. For example, the uranyl silicate, boltwoodite, and the uranyl phosphate, metatorbernite, have formed in contaminated sediments of the Hanford site [2][3][4], uranyl phosphates occur in contaminated soils of the Fernald site [5], and uranyl sulfates are common in altered mine tailings [6]. The interactions of these minerals with aqueous systems, and the details of how they dissolve and precipitate, are integral to understanding and predicting the mobility of uranium.…”
Section: Introductionmentioning
confidence: 99%